Pregnancy-related inappropriate sinus tachycardia: A cohort analysis of maternal and fetal outcomes. (December 2021) - Sharp, Alexander; Patient, Charlotte; Pickett, Janet; Belham, Mark
Background: Little literature exists regarding the syndrome of inappropriate sinus tachycardia during pregnancy. We aimed to further understand the natural history of inappropriate sinus tachycardia in pregnancy, and to explore maternal and fetal outcomes. Methods: A retrospective, observational cohort analysis of 19 pregnant women who presented with inappropriate sinus tachycardia. Results: 42% attended the emergency department on more than one occasion with symptoms of inappropriate sinus tachycardia; 32% required hospital admission and 26% required pharmacological therapy. There were no maternal deaths, instances of heart failure or acute coronary syndrome, and no thromboembolic or haemorrhagic complications during pregnancy. Rates of caesarean section were similar to the background rate of our unit (32% and 27%, respectively). Rates of induction were notably elevated (58% vs 25%). Conclusion: Inappropriate sinus tachycardia in pregnancy is associated with high rates of hospitalization and induction of labour, which may not be mandatory given the clinical findings in this group of women.